Radioactivity Evaluation in Some of Types Powder Baby Milk in Iraqi Market Local - Y. Ali, Ahmed; R. Kahlil, Mohammed; H.A. , Laken (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to study different samples of powdered milk used for breastfeeding for a group of milk samples available in the local Iraqi markets. The research has noticed the difference in the composition of the effect for some types of milk. This difference may be due to the nature and characteristics of each sample. Radioactive activity was known as alpha decay from the uranium 238 series decay. Using a nuclear impact detector SSNTDs (CR-39). The results showed that the highest amount of radon was in the Novalac sample (418.8 Bq.m-3) and the lowest was in the Golden Dialak sample (15.2 Bq.m-3 ). The highest radium content was in the Novalac sample (23.03 Bq.kg-1), and the lowest was in the Golden Dialak sample (0.83 Bq.kg-1 ). All values obtained were within the limits allowed globally.